مقومات الاقتصاد الجزائري في نهاية العهد العثماني: Foundations of the Algerian Economy at the End of the Ottoman Era - مبارك شودار (Journal of North African Economies, 2025)
This researchpaperaims to address the economichistory of the Algerian eyalet and try to research aspects of economic life and its basic components in Algeriaduring the last stage of the Ottoman era, whichis a very sensitive stage becauseitis a transitionalperiodfrom the Ottoman circle to the French occupation circlein 1830 AD, and thisresearchisbased in general on introducing the most important components of the Algerian economyduring a short periodfollowing the fall of the eyalet in the clutches of the French occupation, and thisresearchpaperaims to follow the most important developmentswitnessed by the Algerian economyduring the Verycriticalhistory, by addressing the most important basic pillars of the Algerian economy and its components, including the agricultural and agricultural field, industry and commercial movement, whether local or international, and trying to track the developments and fluctuations witnessed by the Algerian economicsectorduring the las